EFEKTIVITAS SAKRAMEN INISIASI: Kesatuan Perayaan Ritual dan Tindakan Real - Nadeak, Largus (LOGOS, 2008)
The sacraments of Christian initiation: Baptism, Confirmation, and the Eucharist lay the foundations of every Christian life. The faithful are born anew by Baptism, strengthened by the sacrament of Confirmation, and receive in the Eucharist the food for eternal life. The sacraments of Christian initiation become effective (as medium of salvation), when ritual celebration of these sacraments unites with real act of the faithful. The grace accepted in ritual celebration must bear fruit in the real act. Man/woman who has received the sacraments of Christian initiation asks, “What deed must I do?” Baptism guides someone to live with and in Christ and be called to provide the truth. Confirmation brings someone to be a faithful witness of Christ. Eucharist makes someone renew always his/her faithfulness as a disciple of Christ by doing solidarity. Thus the sacraments of initiation guide faithful to a community where God lives.